Natural killer cell activity as a biomarker for the diagnosis of lung cancer in high-risk patients. Issue 6 (June 2022) - Borg, Morten; Wen, Sara Witting Christensen; Hansen, Torben Frøstrup; Jakobsen, Anders; Andersen, Rikke Fredslund; Hilberg, Ole; Weinreich, Ulla Møller; Nederby, Line
Objective: Natural killer (NK) cells play an essential role in the immune response against cancer. However, immune escape mechanisms may cause inferior NK cell activity (NKA) in patients with cancer. This prospective study examined the relationship between NKA and lung cancer in a high-risk cohort. Methods: In a cohort study, 250 participants referred by their general practitioner for suspicion of lung cancer were included. Before clinical investigation, blood was collected into NK Vue tubes, and the level of interferon gamma after 24 hours served as a surrogate marker for NKA. Results: Among 250 patients, 79 were diagnosed with lung cancer. No difference in NKA was found between patients with lung cancer and control participants in which lung cancer was ruled out (median 226 pg/mL vs. 450 pg/mL). However, there was a significant difference in NKA between patients with late-stage lung cancer and controls (median 161 pg/mL vs. 450 pg/mL). A linear regression model showed that NKA was not influenced by age, sex or smoking status. Conclusions: The significantly lower NKA in patients with late-stage lung cancer warrants further investigation combining NKA with other biomarkers and examining the potential role of NKA as a marker of disseminated disease.